Long-term exposure to moderate fine particulate matter concentrations and cause-specific mortality in an ageing society - Lim, Youn Hee; Oh, Jongmin; Han, Changwoo; Bae, Hyun Joo; Kim, Soontae; Jang, Yoonyoung; Ha, Eunhee; Hong, Yun Chul (International Journal of Epidemiology, 2020)
Background: Long-term exposure to particulate matter <2.5 μm in size (PM2.5) is considered a risk factor for premature death. However, only a few studies have been conducted in areas with moderate PM2.5 concentrations. Moreover, an ageing society may be more susceptible to environmental exposure and future burden of mortality due to PM2.5. Methods: This study estimates hazard ratios (HRs) for all-cause and cause-specific mortality from long-term exposure to moderate PM2.5 concentrations in the elderly populations of seven cities in South Korea. We also projected nationwide elderly mortality caused by long-term exposure to PM2.5, accounting for population ageing until 2045. Mortality in 1 720 230 elderly adults aged ≥65 years in 2008 was monitored across 2009-16 and linked to modelled PM2.5 concentrations. Results: A total of 421 100 deaths occurred in 2009-16, and the mean of annual PM2.5 concentration ranged between 21.1 and 31.9 μg/m3 in most regions. The overall HR for a 10 μg/m3 increase in a 36-month PM2.5 moving average was 1.024 (95% confidence intervals: 1.009, 1.039). We estimated that 11 833 all-cause nationwide elderly deaths were attributable to PM2.5 exposure. Annual death tolls may increase to 17 948 by 2045. However, if PM2.5 is reduced to 5 μg/m3 by 2045, the tolls may show a lower increase to 3646. Conclusions: Long-term exposure to moderately high levels of PM2.5 was associated with increased mortality risk among the elderly. Thus, PM2.5 reduction in response to the projected ageing-associated mortality in South Korea is critical.
Keywords: Adult; Aged; Aging; Air Pollutants; Air Pollution; Cause of Death; Cities; Environmental Exposure; Humans; Mortality; Particulate Matter; Republic of Korea; Ageing society; burden of mortality; particulate matter; survival analyses